Pemberdayaan Mahasiswa Melalui Pembuatan Buku Saku Tentang Kesehatan Reproduksi Sebagai Media Promosi Kesehatan Pada Remaja SMA - Rusmayadi Rusmayadi; Lina Eta Safitri; Julia Mujahadah Pratiwi; Raudatul Umroh (Jurnal Pelayanan Hubungan Masyarakat, 2023)
Reproductive health greatly determines the fertility of each individual. So it is important for someone to get the right and correct information about reproductive health. The current low level of awareness for healthy living behavior among adolescents and adults is an indicator of the need for correct and clear education, education, information or health promotion. The pocket book is an effective health promotion medium in an effort to create new behaviors. The purpose of this activity is to empower students in making pocket books as a medium for promoting reproductive health. The methods used in this activity are surveys and direct demonstrations. The target of this activity is 38 students of the Bachelor of Nursing study program. As a result of this community service activity, students are focused on making pocket books by paying attention to 3 points, namely the concept of youth, the concept of adolescent reproductive health and reproductive health problems in adolescents. This community service activity encourages students as a youth group to be able to participate actively, so that there is an increase in knowledge related to adolescent reproductive health.